Management of Root-Knot Nematode (Meloidogyne incognita) on Bell Pepper (Capsicum annuum L.) under Green House Condition (Indian Journal of Nematology, 2024)
A trial was conducted under green house condition to study the efficacy of some chemicals as soil fumigation and soil application on plant growth characters and reproduction of M. incognita infecting bell pepper. In this study, chemicals viz. metham sodium at 20 ml /m2, 30 ml /m2, 40 ml /m2, fluensulfone at 5 g/m2, 10 g/m2, 15 g/m2 and carbofuran at 20 g/m2 were applied and suitable control was also maintained for comparison. Observations on plant growth characters (shoot and root length, shoot and root weight) and nematode reproduction factors (number of galls per 5g root, number of egg masses per 5g root, nematode population/200 cc soil)and yield kg/plant were recorded. Results showed that metham sodium @ 40ml/m2 was best treatment to improve the plant growthcharacters, yield and reducing nematode reproduction on bell pepper.